Bone health in type 1 diabetes. Issue 4 (August 2018) - Shah, Viral N.; Carpenter, R. Dana; Ferguson, Virginia L.; Schwartz, Ann V.
Abstract : Purpose of review: This article reviews recent publications on the effect of type 1 diabetes (T1D) on fracture risk, bone mineral density (BMD), bone structure, and bone tissue quality. Possible fracture prevention strategies for patients with T1D have also been reviewed. Recent findings: T1D is associated with substantially elevated fracture risk and modestly low BMD at the femoral neck. However, BMD alone does not explain higher observed fracture risk in T1D. T1D also affects bone macro- and microstructure, characterized by thinner cortices and trabecular bone changes such as thinner and more widely spaced trabeculae. Structural bone deficit is pronounced in the presence of microvascular complications. Tissue-level changes, such as accumulation of advanced glycation endproducts, detrimental alterations of the mineral phase because of low bone turnover, and occlusion of vascular channels in bone by mineralized tissue, are implicated in pathophysiology of bone fragility in T1D. There are no guidelines on screening and prevention of osteoporotic fractures in T1D. Summary: More studies are needed to understand the influence of T1D on structural bone quality and tissue material properties. There is a need for a prospective study to evaluate better screening strategies for diagnosis and treatment of osteoporosis in T1D.